Barriers and facilitators to the use of personal information documents in health and social care settings for people living with dementia: A thematic synthesis and mapping to the COM‐B framework. (12th April 2022) - Clark, Emily; Wood, Fiona; Wood, Suzanne
Abstract: Introduction: People living with dementia experience communication difficulties. Personal information documents, or healthcare passports, enable communication of information essential for the care of a person with dementia. Despite the potential for providing person‐centred care, personal information documents are not ubiquitously used. The Capability Opportunity Motivation—Behaviour (COM‐B) model can be used to understand factors determining individuals' behaviours. Objectives: This study aimed to identify the barriers to and facilitators of the use of healthcare passports for people living with dementia through a systematic review methodology. Methods: A systematic search of six electronic databases was undertaken. Grey literature was searched using three databases. All study types reporting barriers to or facilitators of the use of personal information documents in the care of adults living with dementia in high‐income countries were included. Study quality was assessed using the NICE Quality Appraisal Checklist. Thematic synthesis was used to develop descriptive themes, which were subsequently mapped to the COM‐B framework. Results: Nineteen papers were included. Themes included training, awareness, embedding the process in norms and appreciating the value of the personal information documents. A broad range of barriers and facilitators was identified within each COM‐B domain. Conclusion: This framework provides a starting point for evidence‐informed initiatives to improve the use of personal information documents in the care of people with dementia. Patient and Public Contribution: This is a review of studies and did not involve patients or the public. Review results will guide evaluation of a local personal information document, which will be designed with input from the Dementia Champions Network (includes carers and other stakeholders).